How to prove the following equation by a quick method? \begin{eqnarray} \\\sin ^6x+\cos ^6x=\frac{1}{8}\left(3\cos 4x+5\right)\\ \end{eqnarray}

If I use so much time to expand it and take extra care of the calculation process, I can find the answer. Since it is so easy to get mistakes, I have to try it 3 time to obtain the correct answer. Therefore, I wonder there are other easy ways to deal with this question. Is it right?

Thank you for your attention

  • 4
    $\begingroup$ $x^6+y^6=(x^2+y^2)(x^4-x^2y^2+y^4)$ seems like a first obvious step. $\endgroup$ – Thomas Andrews Oct 28 '13 at 16:52
  • $\begingroup$ @Thomas Andrews, I only know how to use Binomial Expansion. Would you mind giving me the reference for learning the expansion of $x^n+y^n$? Thank you. $\endgroup$ – Casper Oct 28 '13 at 17:02

Using $a^3+b^3=(a+b)^3-3ab(a+b),$


$$=1-3\frac{(2\sin x\cos x)^2}4$$

$$=1-\frac34(\sin^22x)\text{ using }\sin2x=2\sin x\cos x$$

$$=1-\frac34\frac{(1-\cos4x)}2 \text{ using }\cos2y=1-2\sin^2y$$

  • $\begingroup$ @BabakS., thanks. I have rectified one mistake. $\endgroup$ – lab bhattacharjee Oct 28 '13 at 16:57
  • $\begingroup$ Nice Answer~! It is so quick. $\endgroup$ – Casper Oct 28 '13 at 17:38
  • $\begingroup$ @CasperLi, Thanks. hope I could convey the pattern $\endgroup$ – lab bhattacharjee Oct 28 '13 at 17:40

To flesh out Thomas's comment into another answer: start with the factorization $x^3-y^3 = (x-y)(x^2+xy+y^2)$; this can be derived easily from the finite geometric series. Replacing $y$ with $-y$ yields $x^3+y^3 = (x+y)(x^2-xy+y^2)$, and then replacing $x$ with $x^2$ and $y$ with $y^2$ yields $x^6+y^6 = (x^2+y^2)(x^4-x^2y^2+y^4)$. Now, plugging in $x=\cos\theta, y=\sin\theta$ and using $\cos^2\theta+\sin^2\theta=1$ yields $\cos^6\theta+\sin^6\theta = \cos^4\theta-\cos^2\theta\sin^2\theta+\sin^4\theta$. From here, the simplest route is through an approach similar to lab bhattacharjee's answer: $\cos^4\theta-\cos^2\theta\sin^2\theta+\sin^4\theta$ $=(\cos^4\theta+2\cos^2\theta\sin^2\theta+\sin^4\theta)-3\cos^2\theta\sin^2\theta$ $=(\cos^2\theta+\sin^2\theta)^2-3\cos^2\theta\sin^2\theta$ $=1-3\cos^2\theta\sin^2\theta$; and now things proceed exactly as in that answer, using the double-angle formulas for sin and cos in turn.


Using $\cos2A=1-2\sin^2A=2\cos^2A-1,$


Now use $2\cos^22x-1=\cos2(2x)$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.